2017
DOI: 10.1108/jcm-06-2016-1846
|View full text |Cite
|
Sign up to set email alerts
|

When is it necessary to localise product packaging?

Abstract: Purpose The common market practice by global consumer brands to create localised packaging for foreign markets conflicts with findings that cast doubt on this strategy. By examining the differential influence of standard (Western) and local (Chinese) packaging on Chinese consumers’ perceptions and choice behaviour, this study aims to examine whether this strategy is effective or even necessary. Design/methodology/approach A pre-test first identified suitable products and brands. Using a multiple methods appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…It is important to state that these above informational effects derived through servicescape satisfaction led to loyalty intentions at the end, in support of S-O-R theory (Woodworth 1929) and the accessibility-diagnosticity theory (Feldman and Lynch 1988). Finally, we also note that while the accessibility-diagnosticity theory (Feldman and Lynch 1988) has been previously extended to packaging (Khan et al 2017) and branding (e.g., Boisvert 2015;Vaidyanathan 2000), this is the first study of which we are aware that has advanced this theory into the context of servicescape research. The accessibility-diagnosticity theory has been underutilized in marketing and its applicability in this study should encourage further exploration of this theory in relation to servicescape studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is important to state that these above informational effects derived through servicescape satisfaction led to loyalty intentions at the end, in support of S-O-R theory (Woodworth 1929) and the accessibility-diagnosticity theory (Feldman and Lynch 1988). Finally, we also note that while the accessibility-diagnosticity theory (Feldman and Lynch 1988) has been previously extended to packaging (Khan et al 2017) and branding (e.g., Boisvert 2015;Vaidyanathan 2000), this is the first study of which we are aware that has advanced this theory into the context of servicescape research. The accessibility-diagnosticity theory has been underutilized in marketing and its applicability in this study should encourage further exploration of this theory in relation to servicescape studies.…”
Section: Discussionsupporting
confidence: 71%
“…We now turn to the accessibility-diagnosticity theory (Feldman and Lynch 1988) to underpin our model. Packaging research has frequently utilized this theory to account for the effect on consumer behaviors that results from the information the packaging conveys (e.g., Khan et al 2017); we extend this theory into the servicescape literature. Feldman and Lynch (1988, p. 429) indicated that consumers use "the most accessible cognition sufficient to determine a response," as long as that cognition is perceived as relevant to the evaluation at hand (Meyvis and Janiszewski 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research investigating the marketing aspect of packaging, provide an evidence that there is broad consensus among researchers that packaging design (shape, logo, size, color, language, etc.) affects the consumer purchase decision (Nesselhauf et al , 2017; Khan, Lockshin, Lee and Corsi, 2017; Khan, Lee and Lockshin, 2017; Kumar and Kapoor, 2017; Rundh, 2016; Ghosh 2016; Nilforushan and Haeri, 2015; Borishade et al , 2015; Ahmed et al , 2014; Poturak, 2014; Adofo, 2014; Mamo, 2014; Deng and Srinivasan, 2013; Ahmad et al , 2012; Cahyorini and Rusfian, 2011). Furthermore, consumer product companies carry out frequent research to stress the importance of packaging, especially in the context of usage convenience (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of English language is considered as novel, exotic and appealing to consumers, regardless of language proficiency Khan et al (2017aKhan et al ( , 2017b…”
Section: Dutch Dutch Consumers' Evaluation Of Language In Advertisingmentioning
confidence: 99%
“…Packaging is an important criterion for consumer' choice of brands (Khan et al, 2017a(Khan et al, , 2017b. Supermarket scans indicated that the majority Western brands are available in both global (English) and local language (Urdu, Chinese) packaging in Pakistan and China, respectively.…”
Section: Introductionmentioning
confidence: 99%